Antenatal Corticosteroids and Respiratory Distresses Outcome in Preterm Neonates - Fatma Mohamed; Badr El Din Mesbah; Abdelmoneim Khashana (Mashhad University of Medical Sciences, 2021)
Background: The value of antenatal corticosteroid regimen in lessening respiratory distress risk in preterm neonates has been well known, and accordingly, antenatal corticosteroid therapy was recommended for any pregnant woman likely to deliver between 24 and 34 weeks of gestation. Therefore, this study aimed to assess the association between the administration of antenatal corticosteroids within the ideal interval of one week before birth and the outcomes of preterm neonates. Methods: This prospective cohort study included 80 preterm neonates admitted to the neonatal intensive care unit with gestational age from 32 to 37 complete weeks at Suez Canal University Hospitals, Ismailia, Egypt. The newborns were then divided into groups A (did not receive antenatal corticosteroids; n=40) and B (received antenatal corticosteroids; n=40). Results: Severe respiratory distress syndrome was significantly less frequent in group B  (P<0.05) with lower levels of need for oxygen supplementation (P<0.05). Conclusion: Neonates who received antenatal corticosteroids developed less severe respiratory distress, compared to neonates who did not receive this medication. The results favored the use of antenatal corticosteroids to prevent respiratory distress when administrated within the ideal interval of one week before birth.